Flexible and Electroactive Textile Actuator Enabled by PEDOT:PSS/MOF-Derivative Electrode Ink - Wu, Yanxiao; Yang, Ying; Li, Cheng; Li, Yunbo; Chen, Wei (Frontiers in Bioengineering and Biotechnology, 2020)
Smart fabrics that integrate electronic devices with textiles are emerging as potential candidate for apparel and electronics industries. Soft actuators based on conducting polymers are promising for smart fabrics because of light weight, flexibility, and large deformation under low voltage. However, due to the distinct characteristics of textile and electronic components, the connection between textiles and electronic devices still keeps a challenge in development of smart fabrics. Here, we report an new strategy to prepare a flexible and electroactive textile actuator. The fabric electrolyte was directly coated with an electrode ink, which is composed of Poly(3,4-ethylenedioxythiophene):poly(styrenesulfonicacid) doped with carbonized carbon nanotubes wired zeolite imidazolate framework-8 composite. A pre-treatment of the fabric was made by soaking hydrophobic poly(vinylidene fluoride-co-hexafluoropropylene) to increase the ionic conductivity (6.72 mS cm-1) and prevent the electrode ink from penetrating through the fabric. It was found that the textile actuator could work in air stably under a low voltage of 3 V and operate at frequencies from 0.1-10 Hz with large peak-to-peak strain (0.57% at 0.1 Hz), fast strain rate (5.60% s-1 at 10 Hz) and good blocking force (0.62 mN at 0.1 Hz). The key to high performance originates from high ionic conductivity of fabric electrolyte and large specific surface area, good mechanical properties of the metal-organic framework derivative-based composite electrodes, which present insights into preparing other smart fabrics such as textiles sensors, flexible displays and textile energy storage devices.